2014
DOI: 10.3390/coatings4030630
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity Analysis and Lifetime Testing of Suspension Plasma-Sprayed Thermal Barrier Coatings

Abstract: Suspension plasma spraying (SPS) has become an interesting method for the production of thermal barrier coatings for gas turbine components. The development of the SPS process has led to structures with segmented vertical cracks or column-like structures that can imitate strain-tolerant air plasma spraying (APS) or electron beam physical vapor deposition (EB-PVD) coatings. Additionally, SPS coatings can have lower thermal conductivity than EB-PVD coatings, while also being easier to produce. The combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 30 publications
5
57
1
Order By: Relevance
“…Thermal conductivity of YSZ obtained in this work was similar to the trend reported by Pawlosky et al [42] & Curry et al [37,43] on suspension plasma sprayed YSZ coatings. In the case of standard APS sprayed YSZ, thermal conductivity decreases with increase in temperature up to 800ºC and then begins to increase due to sintering effects.…”
Section: Accepted M Manuscriptsupporting
confidence: 80%
See 2 more Smart Citations
“…Thermal conductivity of YSZ obtained in this work was similar to the trend reported by Pawlosky et al [42] & Curry et al [37,43] on suspension plasma sprayed YSZ coatings. In the case of standard APS sprayed YSZ, thermal conductivity decreases with increase in temperature up to 800ºC and then begins to increase due to sintering effects.…”
Section: Accepted M Manuscriptsupporting
confidence: 80%
“…SEM micrograph of TCF failed single layer YSZ in Fig. 10(a) showed that spallation occurred at the bond coat and YSZ interface, which is the common mode of failure observed in suspension plasma sprayed coatings [37][38][39].…”
Section: Thermo Cyclic Fatigue Testmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this microstructure, the thermal conductivity of SPS coatings is in a similar range with that of APS porous coatings and lower than the one of APS segmented coatings. The thermal shock resistance and thermal cyclic performance of the SPS coatings can be excellent (Ref 23,24). Recently, it also was discovered that the SPS process allows the formation of columnar structures.…”
Section: Segmented and Columnar Coatings By Suspension Plasma Sprayingmentioning
confidence: 99%
“…Columnar microstructures produced by suspension plasma spraying (SPS) are of significant commercial interest as SPS offers a cheaper alternative than the conventionally used electron-beam physical vapor deposition (EBPVD) process, whereas the coatings' thermal conductivity and lifetime are preserved or even improved (Ref [13][14][15][16]. Multilayered TBCs produced by SPS are of high relevance for the gas turbine industry as they can allow higher combustion temperatures and enhanced functional performances.…”
Section: Introductionmentioning
confidence: 99%